Age and Body Mass Index Influence Recovery Time of Consciousness After Curettage Under General Anesthesia with Total Intravenous Anesthesia - Siti Aisyah; Supriyadi Supriyadi; Endiyono Endiyono; Tati Hardiyani (FORIKES, 2026)
Curettage is a gynecological procedure commonly performed under general anesthesia using the total intravenous anesthesia (TIVA) technique; however, recovery time after anesthesia may vary among patients. This variation is influenced by patient characteristics, particularly age and body mass index (BMI). This study aimed to analyze the association between age and body mass index with recovery time in post-curettage patients undergoing general anesthesia with the TIVA technique. This study employed a quantitative method with an observational analytic cross-sectional design conducted in the Post Anesthesia Care Unit of RSU PKU Muhammadiyah Aghisna Kroya. A total of 36 patients were selected using purposive sampling. Data on age and BMI were obtained from medical records, while recovery time was assessed using the Modified Aldrete Score and categorized as fast (≤15 minutes) or slow (>15 minutes). Data analysis was performed using Fisher’s Exact Test. The results showed a significant association between age and recovery time (p < 0.001) and between BMI and recovery time (p = 0.007). This study concludes that patients aged <35 years and those with normal body mass index (18.5–22.9 kg/m²) tend to experience faster recovery time (≤15 minutes), whereas older patients and those with higher body mass index are more likely to experience delayed recovery after curettage under general anesthesia using the TIVA technique.Keywords: age; body mass index; recovery time; curettage; total intravenous anesthesia